How Long Does Craving Predict Use of Methamphetamine? Assessment of Use One to Seven Weeks After the Assessment of Craving - Gantt P. Galloway; Edward G. Singleton; The Methamphetamine Treatment Project Corporate Authors (SAGE Publishing, 2008)
Aims: This study lays the foundation for a clinical prediction model based on methamphetamine craving intensity and its ability to predict the presence or absence of within-treatment methamphetamine use.Design: We used a random effects logistic approach for estimating repeated-measures, generalized linear mixed models (GLMM) using craving as the sole predictor of methamphetamine. A multivariate GLMM included craving, length of treatment, treatment assignment, and methamphetamine use the previous week as covariates to control for potential confounds. We performed receiver operating characteristic (ROC) analyses to evaluate predictive accuracy. We investigated further whether methamphetamine craving predicted subsequent use more accurately at intervals more proximal to versus those more distal to assessment, examining one-week periods ending one to seven weeks after assessment of craving.Setting: The study was part of the Center for Substance Abuse Treatment (CSAT) Methamphetamine Treatment Project (MTP).Subjects: Analyses were based on data from 691 methamphetamine dependent outpatients enrolled in the MTP.Measurements: Craving was assessed by self-report on a 0-100 scale. Self-reported methamphetamine use was toxicologically verified. Craving and drug use were assessed weekly for 8 weeks.Findings: In the univariate analysis craving predicted methamphetamine use in the week immediately following the craving report (p <0.0001), with subject-specific use increasing 0.38% for each one-point increase in craving on a 0-100 scale. In the multivariate analysis the probability of use decreased by 2.45% for each week in treatment, increased by 33.11% for previous methamphetamine use, and the probability of methamphetamine use still increased with craving, rising 0.28% for each one-point increase in craving score (all p <0.0001). Predictive accuracy was strongest at the one-week time-lag and declined in magnitude the more distal the assessment period.Conclusions: Craving is a predictor of within-treatment methamphetamine use. Intensity of craving is appropriate for use as a surrogate marker in methamphetamine dependence.